RESEARCH AGENDA OF SHARIAH-COMPLIANT INVESTMENT USING BIBLIOMETRIC ANALYSIS R STUDIO - Afif, Muhammad Zhafir; Sulaiman, Haryaman Justisia; Amelia, Tiara (LPPM STIE Muhammadiah Bandung, 2024)
Research in the financial industry is becoming more diverse as technology and financial investment products develop. Sharia concepts in financial investment products will be assessed in the context of current financial trends, challenges, and future market opportunities. This study aims to provide an overview of these three things using Systematic Literature Reviews of previous studies. This study's findings can inform future Sharia financial product studies and financial market stakeholders' policy and decision-making